GE_GERICHTE A/1940/2021 vom 11. Oktober 2016 - GE Cour de justice (2016)
MESURE DE CONTRAINTE(DROIT DES ÉTRANGERS) | LEI.5.al1.letd; LEI.64a; LEI.64d.al2.leta; LEI.75.al1.letc; LEI.76.al1.letb.ch1; LEI.76.al1; LEI.76a.al2.lete; LEI.76a.al3.leta